Effect of the pretreatment with acerola (Malpighia emarginataDC.)juice on ethanol-induced oxidative stress in miceeHepatoprotectivepotential of acerola juice - Rochette, Neuza Félix Gomes (2021)
Background and objectives:Acerola (Malpighia emarginataDC.) is a tropical fruit known for its nutritionaland functional properties due to its great contents vitamin C, carotenoids and anthocyanins. The anti-oxidant potential from plants extracts associated to hepatoprotective activity has been widely studied.However, the effect of antioxidants in natural fruit juice has not been fully searched. The aim of this workwas to investigate the antioxidant properties of acerola juice and its hepatoprotective potential againstacute ethanol-induced stress.Materials and methods:Ripe acerola were collected, processed into juice and initially analyzed to anti-oxidant propertiesin vitro. Afterwards,in vivohepatoprotective activity was evaluated in mice. Theanimals received the juice by gavage as pretreatment for 15 consecutive days and then, were submittedto ethanol-induced stress in single dose (5 g/kg). The activities of serum enzymes as well as lipid per-oxidation degree were evaluated. The activities of serum marker enzymes for liver damage as well aslipid peroxidation degree were evaluated.Results:Acerola juice presents great vitamin C (1799.5 mg/100 g FW) and total phenolic (188.4 mg GAE/100 g FW), anthocyanins (9.2 mg/100 g FW),flavonols (7.8 mg/100 g FW) contents and high activity ofsuperoxide dismutase (1053.6 UA/g DM) with a total antioxidant activity of 137.5mmol Trolox/g FW. Thejuice treatment inhibited lipid peroxidation and reduced the activities of aminotransferases (p 0.05), inmice liver.Conclusion:These results indicate that acerola juice is able to prevent the hepatic damage induced byethanol, probably as a result of an enhancement of the antioxidant status in the animals